Common genetic variation in KATNAL1 non‐coding regions is involved in the susceptibility to severe phenotypes of male infertility - Cerván‐Martín, Miriam (2022)
© 2022 The Authors. Andrology published by Wiley Periodicals LLC on behalf of American Society of Andrology and European Academy of Andrology. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.